Altered Rest-Activity Patterns Evolve via Circadian Independent Mechanisms in Cave Adapted Balitorid Loaches - Duboué, Erik R.; Borowsky, Richard L. (PLOS ONE, 2012)
Circadian rhythms and rest homeostasis are independent processes, each regulating important components of rest-activity patterns. Evolutionarily, the two are distinct from one another; total rest time is maintained unaffected even when circadian pacemaker cells are ablated. Throughout the animal kingdom, there exists a huge variation in rest-activity patterns, yet it is unclear how these behaviors have evolved. Here we show that four species of balitorid cavefish have greatly reduced rest times in comparison to rest times of their surface relatives. All four cave species retained biological rhythmicity, and in three of the four there is a pronounced 24-hour rhythm; in the fourth there is an altered rhythmicity of 38–40 hours. Thus, consistent changes in total rest have evolved in these species independent of circadian rhythmicity. Taken together, our data suggest that consistent reduction in total rest times were accomplished evolutionarily through alterations in rest homeostasis.